Classroom teaching and learning: space in research science teaching in the early years of elementary education in the current Common National Curriculum Base (BNCC) (Research, Society and Development, 2023)
The classroom is a privileged space for the teaching and learning process of the thematic units of the reference matrix for the teaching of Science established in the current National Common Curricular Base (BNCC) one of the significant changes brought about was about the new curricular organization for the teaching of Sciences that have three thematic units: Matter and Energy, Life and Evolution and Earth and Universe, taught in the classroom learning routines from the early years of elementary school to the early years of elementary school. The objective of the research was to present a theoretical-methodological foundation about the teaching of science by investigation in the early years of Elementary School in the thematic units of Matter and Energy in the methodology of teaching science by investigation. The research methodology was used within the qualitative approach, in the Action-Research procedures; It was found that research-based teaching provided significant and essential learning in the thematic units Matter and Energy; There was greater interaction between students in the theoretical discussion stage of the results obtained regarding the problems posed; It is concluded that the teaching of the teaching contents Matter and Energy in the methodology described above, in addition to favoring the acceleration of learning, presented innovative methodologies for teaching Science to teachers, in addition to promoting scientific literacy of students.